BASIC PSYCHOLOGICAL NEEDS: IMPORTANCE OF BALANCE IN THEIR SATISFACTION FOR SUBJECTIVE WELL-BEING (Annual of the Faculty of Philosophy in Skopje, 2009)
Basic psychological needs are defined as internal conditions essentialfor continuous psychological development, integrity and well-being. They areenergizing states, and their satisfaction is precondition for psychic health andwell-being, while thwarting leads to ill-being. Those needs have inherent rootsand their forming, manifesting and satisfaction are under strong influence bythe social environment. Findings from the research show that increasing intheir satisfaction is followed by increase in the level of well-being. Also, resultsshow that essential for optimal functioning and well-being is, if satisfactionof all needs is in balance.
Keywords: BASIC PSYCHOLOGICAL NEEDS; COMPETENCE; AUTONOMY; RELATEDNESS; SUBJECTIVE WELL-BEING